Recordkeeping and the life‐long memory and identity needs of care‐experienced children and young people. Issue 4 (29th June 2020) - Hoyle, Victoria; Shepherd, Elizabeth; Lomas, Elizabeth; Flinn, Andrew
Abstract: In family settings stories, photographs and memory objects support narratives of identity and belonging. Such resources are often missing for people who were in care as children. As a result, they may be unable to fill gaps in their memories or answer simple questions about their early lives. In these circumstances, they turn to the records created about them by social workers and care providers to reconstruct personal histories. Research suggests that thousands of requests to view records for this purpose are made each year in England under the subject access provisions of data protection legislation. This article reports the findings of MIRRA, a participatory research project on the memory and identity dimensions of social care recordkeeping. Drawing on data collected during interviews and focus groups with adult care leavers, the study explores the motives and experiences of care‐experienced people who access their records in England. Findings show the practical and cultural challenges they face when doing so and the resulting impacts on well‐being. The study suggests that the development of person‐centred approaches to recordkeeping in social work, which focus on the perspectives and experiences of the individual, could better support the lifelong memory and identity needs of care‐experienced people.